Dosimetric properties of lithium borate glass doped with dysprosium. (26th August 2020) - El‐Faramawy, Nabil; El‐Naggar, Ahmed; Woda, Clemens; El‐Kinawy, Mohamed
Abstract: Characterization of thermoluminescence (TL) properties of lithium borate glass samples doped with different concentrations of dysprosium (Dy) was carried out. Samples were prepared using a melting method at 1100°C and irradiated with β‐particles. The glass samples doped with 0.1% Dy displayed the best TL dosimetric properties compared with other compositions. Deconvoluted analyses of the glow curves displayed five overlapping TL glow peaks located between 392.0 and 510.3 K. A good linear TL dose–response for β‐particles was obtained in the dose range 66.6 mGy to 33.3 Gy. The minimum detectible dose was evaluated to be 205.4 μGy and samples revealed thermal fading in 312 h to 29% of their original value. Abstract : The results indicated that the glass samples doped with 0.1% Dy displayed the best TL dosimetric properties compared with other compositions. Deconvoluted analyses of the glow curves displayed five overlapping TL glow peaks located between 392.0 and 510.3 K. A good linear TL dose–response for β‐particles was obtained in the dose range 66.6 mGy to 33.3 Gy. The samples revealed thermal fading in 312 h to 29% of their original value.